Interactive learning kit: photosynthesis ‘Grow a Tree’ / Roziana Bujang … [et al.] - Bujang, Roziana; Mohd Rosli, Nor Habibah; Saipuddin, Siti Fatimah; Yahya, Norihan; Mustapha, Muhammad Firdaus (Universiti Teknologi MARA, Pahang, 2022)
It is important that primary school students understand the principles of science to ensure that they have a strong theory in preparation for a more challenging science syllabus at the secondary level. The objective of this project was to design and develop an interactive learning kit to help introduce basic science concepts to elementary students. ‘Grow A Tree’ interactive learning kit was invented to help teaching and learning in schools. It explains the needs and processes of photosynthesis in plants in detail. Before this interactive learning kit is used, instructors should first explain to students about the needs and full process of photosynthesis. To test the level of understanding of students, students need to complete the charts contained in this kit. This interactive learning kit contains a major chart, a game card and a complete set of answers for instructional reference. The user also will get an apps. to be installed so that this interactive learning kit can be used anywhere easily. It can be used at pre-school to elementary level as it is based on the Primary School Standard Curriculum (KSSR). Parents can also use this teaching aid as a medium to review home-based learning. The ‘Grow A Tree’ photosynthesis is able to nurture and attract students to the subject of science.